Letter (copy) - Citrine, Walter, 1887-1983
012a-0063-001 Secretary's. WMC/FP/483 3rd August, 1938. Senor J.I. de Lizaso, 75, Gloucester Terrace, Hyde Park, London, W.2. Dear Senor Lizaso, With reference to your letter of the 30th July, the only people in America to whom recommendations from me would be of any value would be the officials of the American Federation of Labor. Outside of them I do not know anyone sufficiently well to venture sending a letter of introduction. If you think this would be of any value I will send a letter which Mr. Ramon de la Sota can take with him. Yours sincerely, General Secretary 292/946/12a/63